India's Chandrayaan Missions: Exploring the Moon for Science and Resources - Dr.A.Shaji George (Zenodo, 2023)
India's space program has made rapid advances in recent decades, with a focus on exploring the Moon through the Chandrayaan series of lunar orbiter missions. Chandrayaan-1, launched in 2008, was India's first mission to the Moon. Its objectives included high-resolution mineralogical and chemical mapping, searching for surface or sub-surface water ice, and studying the lunar interior. Chandrayaan-1 operated for 312 days, achieving most of its goals while confirming the widespread presence of water molecules on the Moon before the mission ended prematurely. The Chandrayaan-2 mission aimed to land a rover on the lunar surface to conduct in-situ studies, but the landing attempt in 2019 was not successful. The proposed Chandrayaan-3 aims to try again to land near the lunar south pole, where permanently shadowed craters are believed to contain water ice - a valuable potential resource for sustained lunar habitation. The scientific payloads on Chandrayaan-3 are designed to study lunar topography, mineralogy, elemental abundance, and the subsurface structure down to a depth of 100 m. Chandrayaan-3 will build on the successes and lessons learned from India's previous lunar missions. The overarching scientific objectives are to understand the origin and evolution of the Moon, as well as to assess the presence and accessibility of resources such as water ice. On the technology side, the Chandrayaan program is advancing India's capabilities in launch vehicles, deep space communication, lunar orbit injection, and soft landing systems. Lunar exploration provides opportunities for interplanetary research and prepares for potential future human exploration and utilization. The Chandrayaan missions demonstrate India's commitment to planetary science and leadership in space technology development.